THE STUDY OF EROSION PROCESSES IN THE HILLY AREA OF BUZĂU COUNTY (ROMANIA) IN THE SPECIFIC CLIMATIC CONDITIONS OF YEAR 2022 - Alexandra Teodora RADU; Mariana BURCEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The research was carried out in 2022 in the Valea with Drum hydrographic basin, located on the Buzău county, in the area of Aldeni - Romania. The Station for the Study of Soil Erosion, established in 1971, operates in this perimeter. Starting from the fact that the intensity of the erosion phenomenon is determined by: precipitation, the slope and length of the slopes, the degree of erodibility of the soil and the agricultural practices used, research in the field of erosion has become very important in this area. The research carried out within this stationary follows a complex range of processes such as: quantifying runoff and erosion processes on sloping land produced by torrential rains, the influence of crops and cultivation technologies on erosion processes, on the Chernozem subtype argic. The main objectives of this study were to present and interpret the data regarding the annual rainfall regime and the vegetation period, the study of the rains that produced runoff and erosion, respectively the surface runoff determined by these rains and the annual amount of soil washed from the plots control, differentially cultivated. The analysis of the experimental results shows that the year 2022 was dry, the recorded temperatures exceeded 22.6 0C in the May-September period, out of 46 rains recorded at the station during the summer period, 60.9 % were less than 5 mm. Quantitative and qualitative study of the erosion process allowed the assessment of the amount of material washed from the soil surface (this being 26 t ha-1 on a 15% slope and 28.1 t ha-1 on a 20 % slope recorded in uncultivated plots) by the runoff produced by the rains that fell during the summer.